2020
DOI: 10.1249/mss.0000000000002453
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Reverses Lipotoxicity-induced Cardiomyopathy by Inhibiting HMGCS2

Abstract: Purpose This study aimed to determine the effect of exercise training on preventing lipotoxic cardiomyopathy and to investigate the role of the 3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2) and miR-344g-5p in cardiomyocytes. Methods Male C57BL/6 mice were fed a 60% high-fat diet (HFD) for 12 wk then began swimming exercise or remained sedentary for 8 wk. Thereafter, cardiac function was assessed by echocardiography, and heart tissue and plasma were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Myocardial Hmgcs2 is the rate-limiting enzyme of ketone body production, which promotes the generation of 3-hydroxybutyric acid in the myocardium. However, study has shown that the Hmgcs2 overexpression is related to myocardial lipotoxicity caused by a high-fat diet in mice, and the inhibition of the upregulation of Hmgcs2 can reverse cardiomyopathy induced by lipotoxicity ( Sikder et al, 2018 ; Li et al, 2021 ). Thus, the cardioprotective effect of SGLT2i may not be mediated by upregulation of Hmgcs2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial Hmgcs2 is the rate-limiting enzyme of ketone body production, which promotes the generation of 3-hydroxybutyric acid in the myocardium. However, study has shown that the Hmgcs2 overexpression is related to myocardial lipotoxicity caused by a high-fat diet in mice, and the inhibition of the upregulation of Hmgcs2 can reverse cardiomyopathy induced by lipotoxicity ( Sikder et al, 2018 ; Li et al, 2021 ). Thus, the cardioprotective effect of SGLT2i may not be mediated by upregulation of Hmgcs2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced JPH2 expression levels have also been reported in a mouse model of lipotoxic cardiomyopathy. Male C57BL/6 mice that were fed a 60% high-fat diet for 12 wk developed myocardial hypertrophy, fibrosis, reduced coronary reserve, and suppressed cardiac function ( 253 ). The reduced JPH2 expression levels could be reversed by swimming exercise and silencing of 3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2), suggesting that the cardiomyopathy development itself led to loss of JPH2.…”
Section: Acquired Diseases Caused By Altered Junctophilin Functionmentioning
confidence: 99%
“…HMGCS2 is a key enzyme that controls ketone synthesis [ 35 ]. Expression and activity of HMGCS2 are regulated by several transcription factors and by posttranslational modifications including acetylation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HMGCS2 was also elevated heart tissues from streptozotocin-induced diabetic rat [ 38 ]. Li et al showed that exercise training could reverse lipotoxicity-induced cardiomyopathy by repressing HMGCS2 [ 35 ]. Wang et al demonstrated that silencing of peroxisome proliferator-activated receptor-alpha alleviated myocardial injury in DCM by repressing HMGCS2 expression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%